Who has what? : all about girls' bodies and boys' bodies - Harris, Robie H. (All about us series, 2011)
This series for young children provides easy-to-understand facts and answers. Launching the series is Who Has What?, a simple story following Nellie and Gus on a family outing to the beach. Humorous illustrations, conversations between the siblings, and a clear text all reassure young kids that whether they have a girl's body or a boy's, their bodies are perfectly normal, healthy, and wonderful.